MODEL PENINGKATAN OCB MELALUI SERVANT LEADERSHIP DAN KEPUASAN KERJA - Berty Meitya Ayu Saputri; Budhi Cahyono (Jurnal Ekonomi dan Bisnis, 2016)
ABCTRACTThe purpose of this research is to know and analyze model of OCB improvement throughtservant leadership and job satisfaction. The population in this research is the employees ofPT. Beverly International Pekalongan. The sampling method in this research is used censusmethod with 40 peoples as a total respondent. The analysis method in this research is usedpath analysis. The result of this research shows that: 1) There’s an effect of servant leadershiptoward OCB. 2) There’s an effect of servant leadership toward job satisfaction. 3) There’s aneffect of job satisfaction toward OCB. 4) There’s an effect of servant leadership toward OCBthrought job satisfaction.Keywords: Servant leadership, job satisfaction, Organizational citizenship behavior (OCB